Landasan Moralitas dalam Menutup Aurat pada Mahasiswi - Hasna Nur Azizah; Asep Dudi Suhardini; Giantomi Muhammad (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research was conducted to obtain data on the moral foundations of modesty in clothing among female students at an Islamic higher education institution in Bandung. The study aims to assess moral knowledge, moral feelings, moral behavior, and educational analysis regarding morality as a basis for wearing Islamic attire among female students. The approach used is a quantitative method with survey techniques. The research population consists of female students from the 2020-2023 cohort, with a sample size of 100 individuals. The data analysis technique used is descriptive analysis, which includes calculating average values, finding standard deviations, determining variable classification tables, and drawing conclusions by collecting data through questionnaires, documentation, observations, and interviews. The results indicate that moral knowledge about modesty in clothing falls into the adequate category, with an average score of 51, within the 49-51 interval. Moral feelings about modesty in clothing also fall into the adequate category, with an average score of 47, within the 44-48 interval. Moral behavior in terms of modesty in clothing is categorized as adequate, with an average score of 38, within the 36-38 interval. Therefore, based on knowledge, feelings, and moral behavior as three components indicating good character in the formation of morality among female students related to Islamic attire, it is considered to be in the adequate category. Abstrak. Penelitian ini dilakukan untuk memperoleh data mengenai dasar moral dalam menutup aurat di kalangan mahasiswi di salah satu perguruan tinggi Islam di Bandung. Studi ini bertujuan untuk menilai pengetahuan moral, perasaan moral, perilaku moral, dan analisis pendidikan mengenai moralitas sebagai dasar untuk menutup aurat atau berpakaian Islami di kalangan mahasiswi. Pendekatan yang digunakan adalah metode kuantitatif dengan teknik survei. Populasi penelitian ini terdiri dari mahasiswi angkatan 2020-2023, dan sampelnya terdiri dari 100 orang. Teknik analisis data yang digunakan adalah analisis deskriptif, yang mencakup perhitungan nilai rata-rata, menemukan deviasi standar, menentukan tabel klasifikasi variabel, dan menarik kesimpulan dengan mengumpulkan data melalui kuesioner, dokumentasi, observasi, dan wawancara. Hasilnya menunjukkan bahwa pengetahuan moral mengenai menutup aurat berada dalam kategori cukup, dengan nilai rata-rata 51, yang berada dalam interval 49-51. Perasaan moral tentang menutup aurat juga berada dalam kategori cukup, dengan nilai rata-rata 47, dalam interval 44-48. Perilaku moral dalam menutup aurat dikategorikan sebagai cukup, dengan nilai rata-rata 38, dalam interval 36-38. Oleh karena itu, berdasarkan pengetahuan, perasaan, dan perilaku moral sebagai tiga komponen yang menunjukkan karakter yang baik dalam pembentukan moralitas di kalangan mahasiswi terkait dengan pakaian Islami dianggap berada dalam kategori cukup.